The 'Visualized' macrocycles: Chemistry and application of fluorophore tagged cyclodextrins - Benkovics, Gábor; Malanga, Milo; Fenyvesi, Éva (International journal of pharmaceutics, 2017)
Cyclodextrins are macrocyclic molecules able to form host-guest complexes due to their hydrophobic cavity. Because of their carbohydrate nature they do not absorb light in the UV-vis region (200-800nm), but they can be converted into spectroscopically active compounds via modification with a chromophore unit. Among the chromophores, the group of fluorophores can provide high sensitivity in analytical applications (chemosensing) and low detection limit in optical imaging methods (fluorescent microscopy). Fluorophore-tagged cyclodextrins therefore combine interesting spectroscopic properties with promising supramolecular features which make these conjugates widely applicable in various pharmaceutical fields. The aim of this work is to review the various types of fluorophores which have been used for cyclodextrin tagging, to discuss the synthetic strategies used for the conjugation and to summarize the pharmaceutical applications of these 'visualized' macrocycles including their use in photodynamic therapy. The recent achievements in studying how the fluorophore-appended cyclodextrin derivatives cross biological barriers are also reviewed.
Keywords: Drug delivery; Fluorophore-tagged cyclodextrins; cyklodextriny; Chemosensing; Fluorescent Dyes; Photochemotherapy; Hydrophobic and Hydrophilic Interactions; fotochemoterapie; Fluorescent microscopy; Photodynamic therapy; hydrofobní a hydrofilní interakce; fluorescenční barviva; Cyclodextrins